Nutrition therapy in pediatric burns - Ergül Kunduracı, Yasemin; Garipağaoğlu, Muazzez (Bentham Science Publishers, 2021)
Background: Burns are defined as injuries resulting from exposure to thermal radiation, electrical or chemical exposure of the skin or organic tissues. It has high mortality and morbidity in low and middle-income countries. Objective/Methods: The objective of this study is to evaluate the present knowledge principles of nutritional therapy for pediatric burns from the dietician's perspective, taking into account the epidemiology and physiology of the burn. The purpose of burn treatment is to provide survival and tissue repair and to increase immunity. Therefore, besides fluid electrolyte replacement and surgical interventions, nutritional therapy is quite important. Nutrition principles should aim to reduce inflammation and meet hypermetabolic needs. Results: In the clinical practice of children suffering from burns, daily energy need is calculated by adding the recommended energy expenditure to the burn percentage, but the most accurate method is the use of indirect calorimetry. Protein requirement is around 1.5-3.0 g/kg/day. Carbo-hydrate intake should be 55-60% of total energy intake, while lipids should be less than 30%. Vitamin supplements in the form of a multivitamin are recommended in addition to vitamin A, vitamin C, and Zinc. In cases where oral intake is insufficient, enteral nutrition should be applied as soon as possible. When enteral feeding is contraindicated, parenteral nutrition is preferred. Conclusion: Evaluating the nutritional status of children and meeting macro and micronutrient needs accelerate wound healing, shorten hospital stay, and reduce mortality.
Keywords: Burn; Child Nutrition; Energy Calculation; Nutraceuticals; Nutrition Therapy; Pediatric Burns